2019
DOI: 10.4236/pp.2019.104016
|View full text |Cite
|
Sign up to set email alerts
|

<i>In Vivo</i> Sedative and Anxiolytic Activities of <i>Thunbergia erecta</i> (Acanthaceae) Leaves Activate Gamma-Aminobutyric Acid (GABA) Mediated Hyperpolarizationin Swiss Albino Mice

Abstract: Background: Thunbergia erecta (Acanthaceae) is the most abundant medicinal plant in different parts of Bangladesh where it is known as "nilghonta". It has been used as traditional medicine for insomnia, depression and anxiety management. However, no scientific evidence of T. erecta belonging to neuropharmacological activity has been reported. The aim of present study was to investigate in vivo sedative and anxiolytic activities of methanol extract from the leaves of T. erecta in Swiss Albino mice. Methods: Sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The extract showed significant reduction in sleep latency and increased thiopental sodium induced sleeping time, indicating sedative effect. Thiopental is known to enhance the inhibitory action of the GABA receptor that decreases neuronal activity (Begum et al, 2019). On the other hand, in hole cross test, the results showed dose dependent activity corroborating with the findings of thiopental sodium induced sleeping test.…”
supporting
confidence: 79%
“…The extract showed significant reduction in sleep latency and increased thiopental sodium induced sleeping time, indicating sedative effect. Thiopental is known to enhance the inhibitory action of the GABA receptor that decreases neuronal activity (Begum et al, 2019). On the other hand, in hole cross test, the results showed dose dependent activity corroborating with the findings of thiopental sodium induced sleeping test.…”
supporting
confidence: 79%
“…When passed through humans at approximately 50 kg of body weight, the plants can be taken up to 2500-1 00 000 mg (2.5-100 g) to reach a moderate hazard according to the WHO [15] referring that doses of T. alata and T. erecta extracts under 2.5-100 g, should be saved for consumers. Concerning these data, usages of T. erecta reported [11][12][13]19] in cooking, eating as a vegetable and application of its leaves for a remedy of headache, should be carefully determined for the doses. However, it is not surprise that T. alata leaf extracts can have activity against Pseudomonas aeruginosa and have significant antibacterial activity against Salmonella typhi [20] , according to their biological activities including DNA damage in normal and poisoned PBMCs, which can be assumed to occur at plant concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Bhuiyan et al [12] researched T. erecta, a medicinal plant with many reported phytochemicals and significant medicinal value and revealed that the methanol leaf extract has hypoglycemic effects in an animal model. The most recent research reported experimental results in swiss albino mice with T. erecta, which contained phytoconstituents, flavonoids, glycosides, tannins saponin, carbohydrates and alkaloids and possessed sedative and anxiolytic activity traditionally used in insomnia, depression and anxiety management [13] . Information on the two wellknown, representative species of Thunbergia mentioned above, T. laurifolia and T. grandiflora, is very important for natural methods for human health, which is a longlived concept.…”
mentioning
confidence: 99%
“…Medicinal plants are used to treat a lot of psychiatric disorders through their potential active phytochemicals [25] which have fewer side effects [26]. Since synthetic drugs reduce these disorders with a great number of side effects and sometimes they create addiction over these drugs which causes suicide [27]. To develop a potential neuropsychiatric drug with a tolerable number of side effects [28], we used several animal models for testing medicinal plants chemical constituents' efficacy by following phytochemical and pharmacological analysis [29].…”
Section: Discussionmentioning
confidence: 99%